Effects of Erbium-Doped: Yttrium Aluminum Garnet (Er: YAG) Laser on Bacteremia due to Scaling and Root Planing - Komatsu, Yasutaka; Morozumi, Toshiya; Abe, Daisuke; Okada, Moe; Nakasone, Naohiro; Okuda, Kazuhiro; Yoshie, Hiromasa (Journal of Lasers in Medical Sciences, 2012)
INTRODUCTION: The aims of the present study were: [1] to evaluate whether Erbium-Doped: Yttrium, Aluminum and Garnet (Er: YAG) laser could be a prophylactic methods against transient bacteremia during scaling and root planing (SRP) [2] to confirm the efficacies of SRP with Er: YAG laser by clinical and microbiologic evaluations. METHODS: Twenty chronic periodontitis subjects were randomly treated for quadrant SRP with either conventional hand instrument (n=10) or Er: YAG laser (n=10) monotherapy. Peripheral blood samples were drawn at baseline and 6 minutes after initiation of SRP, and were cultured for the analysis of bacteremia. Clinical measurements of full mouth plaque control record (PCR), probing pocket depth (PPD), clinical attachment level (CAL) and bleeding on probing (BOP) were made at baseline and 1 month after SRP. In addition, microbiologic analyses of subgingival samples were also performed at baseline and 1 month after SRP using the polymerase chain reaction Invader method. RESULTS: The incidence of bacteremia during SRP was 0% (0/10) in the Er: YAG laser group and 80% (8/10) in the hand instrument group, which was significantly different (P = 0.0003). All isolates from blood were facultative or obligate anaerobes and more than half of the microorganisms were species of streptococci. Intragroup comparison revealed that the mean PPD and CAL significantly decreased compared to baseline in both groups (P < 0.05). However, the percentage of BOP positive significantly decreased only in Er: YAG laser group (P = 0.005). In addition, the reductions of the subgingival bacterial counts between baseline and 1 month after SRP were also comparable between the two groups. CONCLUSION: The present study demonstrated that SRP with Er: YAG laser could not only be an alternative treatment for improvement of clinical and microorganisms situations but also a novel prophylactic method against transient bacteremia.